Pengembangan Media Pembelajaran Berbasis E-Book pada Mata Pelajaran Informatika untuk Siswa Kelas XI di MA Al Fattahiyyah - Abdul Adzim Aminulloh; Vertika Panggayuh (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The low level of student motivation and learning outcomes in Informatics at MA Al Fattahiyyah is a key issue that needs to be addressed. This study aims to develop an e-book–based learning medium using Canva to create a more engaging and effective learning experience. The research employs a Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, media design, product development, implementation through small and large group trials, and feasibility evaluation. The research instruments consist of interview guidelines, student needs questionnaires, expert validation sheets, and student response questionnaires. The validation results show a feasibility score of 74% from media experts and 84% from subject matter experts. The small group trial yielded a percentage of 72.27%, while the large group trial reached 83.6%, with an overall average of 78.47%, which falls into the “very feasible” category. These findings indicate that the developed e-book–based learning media is effective in improving students’ learning motivation and their understanding of Informatics material.